1984
DOI: 10.1113/expphysiol.1984.sp002779
|View full text |Cite
|
Sign up to set email alerts
|

Gestation‐dependent Aspects of the Response of the Ovine Fetus to the Osmotic Stress Induced by Maternal Water Deprivation

Abstract: SUMMARYWater deprivation was produced in pregnant sheep by withholding water for 24 h and then giving them 500 ml/d for the subsequent 3 d. All ewes bore chronically cannulated fetuses. Eleven experiments were performed in group I animals (gestation periods of 107-119 d at maximal stress) and eight experiments in group II (126-144 d of gestation). Measurements were made of maternal and fetal plasma osmolalities, fetal urine flow rate and osmolality, amniotic fluid osmolality and fetal plasma antidiuretic hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Maternal water restriction significantly alters maternal and fetal fluid dynamics (3)(4)(5)(6). In the pregnant ewe, dehydrationinduced maternal plasma hyperosmolality and hypernatremia are associated with elevated levels of plasma AVP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal water restriction significantly alters maternal and fetal fluid dynamics (3)(4)(5)(6). In the pregnant ewe, dehydrationinduced maternal plasma hyperosmolality and hypernatremia are associated with elevated levels of plasma AVP.…”
mentioning
confidence: 99%
“…Fetal plasma osmolality and sodium concentrations parallel maternal values, whereas increases in fetal plasma AVP are gestation-dependent (3). The fetus also may exhibit a relative decrease in plasma volume, glomerular filtration rate, and urine production (3)(4)(5). Urinary hyperosmolality, mediated in part by increased plasma AVP, contributes to increased amniotic fluid osmolality (1-3), whereas reduced urine production likely contributes to decreased amniotic fluid volume during dehydration (6).…”
mentioning
confidence: 99%
“…We have suggested previously that the renal function of the premature or growth-retarded neonate might resemble that of the fetus rather than that of the normal newborn, and shown that cortisol has a unique natriuretic effect in the immature ovine fetal kidney (5). The immature fetal kidney is less responsive to endogenous or exogenous AVP than is the kidney of the nearterm fetus (6,7). With the discovery of an endogenous natriuretic peptide of atrial origin (8,9) it seemed to be important to find out whether this peptide exerted any influence over sodium handling by the immature fetal kidney.…”
mentioning
confidence: 99%
“…The association between a relative expansion of blood volume (rate of increase above the 95o% confidence limit of the slope of controls) during maternal dehydration and the presence of hypertonic urine in the fetus suggests that ADH may be involved in this mechanism. The relative expansion of fetal blood volume during maternal dehydration occurred in fetuses close to term and our previous study (Bell et al 1984) showed that a mature fetus has a greater capacity to mobilize ADH in response to an osmotic stimulus than an immature fetus. This study thus suggests that ADH release by the ovine fetus during maternal water deprivation is in response to an osmotic stimulus and not fetal hypovolaemia.…”
Section: Discussionmentioning
confidence: 68%
“…In a previous study (Bell, Congiu, Hardy & Wintour, 1984) it was established that there is a gestational trend in the release of antidiuretic hormone (ADH) by the ovine fetus in response to the osmotic stress induced by maternal water deprivation. The fetal plasma ADH concentration, [ADH], was significantly greater, at a given plasma osmolality, in mature (126-144 d gestation) than immature (107-119 d) fetuses.…”
Section: Introductionmentioning
confidence: 99%